A Case of Ewing Sarcoma Presenting With Cardiac Metastasis. Issue 5 (September 2019) - Murad, Ruba; Bakkar, Rimaa; Sukkar, Rehab; Mahmoud, Fadi; Al-Dairy, Alwaleed
Ewing sarcoma is the second most prevalent primary malignant bone tumor. Metastases from Ewing sarcoma to the heart are very rare. Herein, we present a case of undiagnosed Ewing sarcoma in a 12-year-old boy who presented with metastasis to the left atrium. The mass was prolapsing across the mitral valve. In view of the potential risk of embolization, urgent cardiac surgery was performed before the establishment of a definitive diagnosis. Histopathology was consistent with Ewing sarcoma. Subsequent magnetic resonance imaging revealed a mass in his left fibula. The patient was referred to the oncology center and received chemotherapy. One year later, he is alive with no evidence of recurrent cardiac involvement.